Multicriteria Location Selection of Wastewater Treatment Plant by Fuzzy Analytic Hierarchy Process - Kaya, Ihsan (OLD CITY PUBLISHING INC, 2011)
Wastewater treatment is the process of removing contaminants from wastewater and household sewage. It includes physical, chemical, and biological processes to remove physical, chemical, and biological contaminants. The objective of wastewater treatment is to produce a waste stream (or treated effluent) and a solid waste or sludge suitable for discharge or reuse back into the environment. Location selection for a wastewater treatment plant is an important multicriteria investment decision. During the evaluation of both selection criteria and location alternatives, experts need a tool to manage the uncertainty of the decision process. The theory of fuzzy decision-making is a powerful tool to deal with the uncertainty in case of incomplete or vague information. In this paper, a fuzzy multicriteria decision making methodology is suggested for the selection of wastewater treatment plant location among alternatives. The methodology is based on the analytic hierarchy process (AHP) under fuzziness. It allows the evaluation scores from experts to be linguistic expressions, crisp, or fuzzy numbers. In the application of the proposed methodology, the best location is determined for Malatya in Turkey.
Keywords: Wastewater treatment; fuzzy decision making; AHP; multicriteria; DECISION-MAKING; MANAGEMENT; SUPPORT; Computer Science; Science & Technology - Other Topics